Fluorescence-guided lung nodule identification during minimally invasive lung resections - Tajè, Riccardo; Gallina, Filippo Tommaso; Forcella, Daniele; Vallati, Giulio Eugenio; Cappelli, Federico; Pierconti, Federico; Visca, Paolo; Melis, Enrico; Facciolo, Francesco (Frontiers in Surgery, 2022)
In the last few years the minimally invasive surgery has become the standard routine practice to manage the lung nodules. Especially in the case of the robotic thoracic surgery, the identification of the lung nodules that do not surface on the visceral pleura could be challenging. Therefore, together with the evolution of the surgical instruments to give the best option in term of invasiveness, the lung nodule localization techniques should be improved to reach the best outcomes in terms of safety and sensibility. In this review, we aim to overview all the principal techniques used to detect the lung nodules that do not present the visceral pleura retraction. We investigated the accuracy of fluorescence guided thoracic surgery in nodule detection and the differences among the most common tracers used.